Development of A Storybook Based on Adat Basandi Syara', Syara' Basandi Kitabullah (Abs-Sbk) to Strengthen the Minangkabau Philosophy Alam Takambang Jadi Guru at Paud Al-Fa’izin - Emelda, Emelda; Priyanti, Nita (Kirana Publisher (KNPub), 2025)
This research was motivated by the need for culturally relevant learning resources at PAUD AL-FA’IZIN to strengthen children's understanding of local values. Observations indicated that early childhood learners still face difficulties in understanding and internalizing the philosophical values of Minangkabau culture, particularly Adat Basandi Syara’, Syara’ Basandi Kitabullah (ABS-SBK), with a special focus on Alam Takambang Jadi Guru. Existing learning materials have not fully integrated these values into daily teaching and learning activities. Therefore, this study aimed to develop an ABS-SBK-based storybook as a contextual and engaging learning medium for children. The research used a Research and Development (RnD) approach, employing the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation). Data were collected through interviews, observations, and questionnaires involving teachers, parents, and experts in education and culture. The storybook was developed using narratives that incorporate ABS-SBK values and illustrations appropriate to early childhood developmental stages. Validation results showed that the storybook is feasible and has a high level of readability. Teachers and parents responded positively, and children demonstrated improved understanding and application of these values. The study concludes that the storybook is an effective learning medium for strengthening cultural identity from an early age.